(untitled) (Malaysian Journal of Applied Linguistics (MJoAL), 2025)
This study aims to examine the extent to which Malay speakers substitute the voiced /ð/ and voiceless dental /θ/ fricative sounds in the English language with /t/ and /d/ sounds and analyse how Malay speakers perceive the pronunciation of the voiced and voiceless dental fricative sounds. In this study, observation analysis will be adopted, as proposed by Rahman and Hassan (2019). Through the observation analysis and a focus group interview, it was found that the participants mostly substituted the voiceless dental fricative sounds as /t/ and /d/ for voiced dental fricative sounds. With the absence of both voiced and voiceless and dental fricative sounds from the Malay language, the participants try to find the nearest sound that resembles their first language. They had also shared that learning the accurate pronunciation would be beneficial in increasing their knowledge in the English language. In supplementing students’ knowledge in the standard pronunciation, more exposure should be given with authentic material to ensure they get the best resources for learning accurate pronunciation.